Corporate entrepreneurship and organisational performance in the information and communications technology industry - Nkosi, Thokozani (My University, 2012)
Corporate Entrepreneurship (CE) has long been recognised as a potentially viable means for promoting and sustaining corporate competitiveness (Covin & Miles 1999). Turbulence and rapidly changing knowledge - especially in the Information and Communications Technology sector (ICT) - has forced companies to become more entrepreneurial in order to capitalise on new business opportunities and to create value. The research study was quantitative and data was collected through an online survey, which used closed-ended questionnaires. The questionnaires entail assessing the degree of CE in an organisation in relation to its performance. The analysis had 114 samples of companies in the ICT sector. The study indicated that there is a strong positive association between level of CE and company performance. Companies that sustain their businesses and are able to prosper are likely to have a high level of CE. The most important contribution of this study is the testing of CE theories in the South African context. The ICT managers can contribute to entrenching CE by being the champions in creating the environment that stimulates entrepreneurial behaviour.
Keywords: Entrepreneurship; Organisational performance; Competitiveness; ICT sector